Ombudsman/woman/person or else- a gender sensitive dispute - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In an era of the greatest opportunities and the widest range of human rights and freedoms, their implementation is becoming increasingly questionable. It is forgotten that the existence and implementation of one person's rights is limited by the existence and implementation of the same or another right of another person. This does not mean that rights are in any way divided or diminished, but that the holders of rights must be aware that they are members of a community, within which everyone is equal in rights and obligations.One of the mechanisms for establishing full equality between men and women is the use of gender-sensitive terminology, which is primarily reflected in the use of nouns that are designated - in the feminine gender, which prevents discrimination and gives the impression and invitation to women to enter professions that have traditionally belonged exclusively to men.The paper discusses one such debate, which directly concerns people who work in area of the protection of human rights, and how human rights defenders themselves, as well as other lawyers and linguists, view this subtle, yet significant linguistic change in the designation of this important profession. Also, in this paper we raise some methodological questions, and we point out some paradoxes that arise when strictly applying this (or any other) right and obligation (meaning here, while using gender-sensitive terminology).
Keywords: ombudsman, ombudswoman, ombud, gender sensitive, language